HERMENEUTISCHE ÜBERLEGUNGEN ZU HEIDEGGERS „SCHWARZEN HEFTEN“ UND ZUM NEUDENKEN SEINES DENKWEGS (I) - István M. FEHÉR (Studia Universitatis Babeș-Bolyai. Philosophia, 2021)
Hermeneutical Considerations on Heidegger’s Black Notebooks and on the Revisiting of his Path of Thinking (I). Starting with preliminary philological-hermeneutical considerations concerning the way Heidegger’s Black Notebooks can and should be dealt with, as well as concerning the question what tasks may be derived from them for future research, the paper attempts to discuss the Black Notebooks applying a variety of methods and multiple approaches. Themes that are discussed at more or less length include: Time factor and the formulation of our task; explanation and understanding or the way a philosophical path should be approached and dealt with methodically (hermeneutically); the theme related to “Heidegger and anti-Semitism” and the question concerning individuality; prejudices from a hermeneutical perspective and the way to deal with them; relapses and their philosophical explanation; missing and increased sensibility; Heidegger and Hegel; equivocality and the dark side of the “formal indication”; Lukács, Scheler and the devil; Heidegger’s great being-historical treatises and their greatness; suggestions for a reconsideration of Heidegger’s way of thinking. -- One important hermeneutical claim brought to bear on the various discussions is this: just as it would be in-appropriate in our dealing with Heidegger’s texts to disregard Heidegger’s own self-interpretations, it would be no less inappropriate to consider those self-interpretations--which themselves call for interpretation--as telling us the sole and ultimate truth.